Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

After some algebra, Wolfram online integrator gave me the following: $$\tag{1} \int (1-a-t)^{N-2}\ \sqrt{2t-t^2}\ \text{d} t = c\ \cdot t^{3/2}\ \operatorname{F}_1 \left( \frac{3}{2}; -\frac{1}{2}, 2-N; \frac{5}{2}; \frac{t}{2}, \frac{t}{1-a}\right)+C$$ where:

  • $\operatorname{F}_1$ is the Appell hypergeometric function of two variables defined by the expansion: $$\operatorname{F}_1(\alpha; \beta, \beta^\prime ; \gamma; x,y):= \sum_{m,n=0}^\infty \frac{(\alpha)_{m+n}\ (\beta)_m\ (\beta^\prime)_n}{m!\ n!\ (\gamma)_{m+n}}\ x^m\ y^n$$ ($(a_k):=\frac{\Gamma (a+k)}{\Gamma(a)}$ is the Pochhammer symbol), which converges in the region $|x|,|y|<1$;
  • $N\geq 3$ an integer, $a\in ]0,1[$ and $t\in [0,1-a]$ (so the RHside makes sense);
  • $c=c(a,N)$ is a known constant and $C$ is an arbitrary constant (coming from indefinite integration).

My question is:

How can I get (1) without using any software?

I suppose a series expansion of the integrand and term by term integration should be used, but I could not figure out how to do explicit computations. Neither I succeeded in simplifying the derivative of the LHside to get the integrand...

Any hint will be appreciated.

share|cite|improve this question

It is an application of following integral formula for $\operatorname{F}_1$ : $$\operatorname{F}_1(a;b_1,b_2;c;z_1,z_2)=\frac{\Gamma(c)}{\Gamma(a)\Gamma(c-a)}\int_0^1 x^{a-1}(1-x)^{c-a-1}(1-x z_1)^{-b_1}(1-x z_2)^{-b_2}\,dx$$

giving : $$\operatorname{F}_1 \left( \frac 32; -\frac 12, 2-N; \frac 52; \frac t2, \frac t{1-a}\right)=\frac{\Gamma(\frac 52)}{\Gamma(\frac 32)}\int_0^1 x^{\frac 12}\left(1-x \frac t2\right)^{\frac 12}\left(1-x \frac t{1-a}\right)^{N-2}\, dx$$

$$=\frac 32 t^{-\frac 12-1}\int_0^t y^{\frac 12}\left(1-\frac y2\right)^{\frac 12}\left(1-\frac y{1-a}\right)^{N-2}\, dy$$

$$=t^{-\frac 32} C_1\int_0^t \sqrt{2y-y^2}\left(1-a-y\right)^{N-2}\, dy$$

i.e. your result (with $\frac 1c=C_1$ 'absorbing' the constants involved).

Hoping this helped,

share|cite|improve this answer
Thanks a lot Raymond... As you can see below I found also a different solution. – Pacciu May 31 '12 at 17:59
@Pacciu: Fine! So that you'll have a proof from integrals and sums point of view! – Raymond Manzoni May 31 '12 at 19:51
up vote 2 down vote accepted

I found also the following term-by-term integration solution.

One has: $$(1-a-t)^{N-2}\ \sqrt{2t-t^2} = \sqrt{2}\ (1-a)^{N-2}\ \sqrt{t}\ \left( 1-\frac{t}{1-a}\right)^{N-2}\ \sqrt{1-\frac{t}{2}}$$ and by the binomial theorem: $$\begin{split} \left( 1-\frac{t}{1-a}\right)^{N-2} &= \sum_{k=0}^{N-2} (-1)^k\ \binom{N-2}{k}\ \left(\frac{t}{1-a}\right)^k\\ &= \sum_{k=0}^{N-2} \frac{(2-N)_k}{k!}\ \left(\frac{t}{1-a}\right)^k\\ &= \sum_{k=0}^\infty \frac{(2-N)_k}{k!}\ \left(\frac{t}{1-a}\right)^k\\ \sqrt{1-\frac{t}{2}} &= \sum_{k=0}^\infty (-1)^k\ \binom{1/2}{k}\ \left( \frac{t}{2}\right)^k\\ &= \sum_{k=0}^\infty \frac{(-1/2)_k}{k!}\ \left( \frac{t}{2}\right)^k\; ; \end{split}$$ now, since both series in the rightmost sides converge absolutely, Mertens theorem applies and one can take the Cauchy product: $$\begin{split} \left( 1-\frac{t}{1-a}\right)^{N-2}\ \sqrt{1-\frac{t}{2}} &= \left( \sum_{k=0}^\infty \frac{(2-N)_k}{k!}\ \left(\frac{t}{1-a}\right)^k\right)*\left( \sum_{k=0}^\infty \frac{(-1/2)_k}{k!}\ \left( \frac{t}{2}\right)^k\right)\\ &= \sum_{k=0}^\infty \sum_{h=0}^k \frac{(2-N)_h}{h!}\ \left(\frac{t}{1-a}\right)^h\ \frac{(-1/2)_{k-h}}{(k-h)!}\ \left( \frac{t}{2}\right)^{k-h}\\ &= \sum_{k=0}^\infty \sum_{h=0}^k \frac{(2-N)_h\ (-1/2)_{k-h}}{h!\ (k-h)!}\ \frac{1}{2^h\ (1-a)^{k-h}}\ t^k \end{split}$$ with the rigthmost side converging absolutely and uniformly on compact subsets. Therefore one gets: $$(1-a-t)^{N-2}\ \sqrt{2t-t^2} = \sqrt{2}\ (1-a)^{N-2}\ \sum_{k=0}^\infty \sum_{h=0}^k \frac{(2-N)_h\ (-1/2)_{k-h}}{h!\ (k-h)!}\ \frac{1}{2^h\ (1-a)^{k-h}}\ t^{k+1/2}$$ and a rearrangement of the RHside yields: $$(1-a-t)^{N-2}\ \sqrt{2t-t^2} = \sqrt{2}\ (1-a)^{N-2}\ \sum_{m,n=0}^\infty \frac{(2-N)_m\ (-1/2)_n}{m!\ n!}\ \frac{1}{2^m\ (1-a)^n}\ t^{m+n+1/2}\; ;$$ thus term-by-term integration shows that: $$\begin{split} \int (1-a-t)^{N-2}\ \sqrt{2t-t^2}\ \text{d} t &= \sqrt{2}\ (1-a)^{N-2}\ \sum_{m,n=0}^\infty \frac{(2-N)_m\ (-1/2)_n}{m!\ n!}\ \frac{1}{2^m\ (1-a)^n}\ \int t^{m+n+1/2}\ \text{d} t\\ &= \sqrt{2}\ (1-a)^{N-2}\ \sum_{m,n=0}^\infty \frac{(2-N)_m\ (-1/2)_n}{m!\ n!\ (3/2 +m+n)}\ \frac{1}{2^m\ (1-a)^n}\ t^{m+n+3/2}\ + C\\ &= \frac{2\sqrt{2}}{3}\ (1-a)^{N-2}\ \sum_{m,n=0}^\infty \frac{(3/2)_{m+n}\ (2-N)_m\ (-1/2)_n}{m!\ n!\ (5/2)_{m+n}}\ \frac{1}{2^m\ (1-a)^n}\ t^{m+n+3/2}\\ &\phantom{=} +C\\ &= \frac{2\sqrt{2}}{3}\ (1-a)^{N-2}\ t^{3/2}\ F_1\left( \frac{3}{2}; -\frac{1}{2}, 2-N; \frac{5}{2}; \frac{t}{2}, \frac{t}{1-a}\right) +C \end{split}$$ because: $$\frac{3}{2}\ \frac{1}{m+n+3/2} = \frac{(3/2)_{m+n}}{(5/2)_{m+n}}\; .$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.